Leptospira Survey in Wild Boar (Sus scrofa) Hunted in Tuscany, Central Italy - Giovanni Cilia; Fabrizio Bertelloni; Marta Angelini; Domenico Cerri; Filippo Fratini (Pathogens, 2020)
Leptospirosis is a re-emerging, worldwide zoonosis, and wild boar (Sus scrofa) are involved in its epidemiology as the reservoir. The aim of this study was to investigate the prevalence of Leptospira with serological, bacteriological, and molecular assays in wild boar hunted in Tuscany (Italy) during two hunting seasons. In total, 287 specimens of sera, kidneys, and liver were collected to perform microscopic agglutination tests (MATs), isolation, and RealTime PCR to detect pathogenic (lipL32 gene), intermediate (16S rRNA gene), and saprophytic (23S rRNA gene) Leptospira. Within sera, 39 (13.59%) were positive to the MAT, and Australis was the most represented serogroup (4.88%), followed by Pomona (4.18%), and Tarassovi (3.14%). Moreover, four Leptospira cultures were positive, and once isolates were identified, one was identified as L. borgpetersenii serovar Tarassovi, and three as L. interrogans serovar Bratislava. Pathogenic Leptospira DNA were detected in 32 wild boar kidneys (11.15%). The characterization through the amplification of the rrs2 gene highlighted their belonging to L. interrogans (23 kidneys), L. borgpetersenii (four), and L. kirschneri (one), while nine kidneys (3.14%) were positive for intermediate Leptospira, all belonging to L. fainei. The results of this study confirmed the importance of wild boar in the epidemiology of leptospirosis among wildlife in Central Italy.